1998
DOI: 10.1017/s0033291798006540
|View full text |Cite
|
Sign up to set email alerts
|

The effect of personality on withdrawal severity and taper outcome in benzodiazepine dependent patients

Abstract: These findings indicate that clinical decisions on how to manage BZ tapering should be guided by personality assessments, in addition to the usual considerations of BZ dosage, residual psychopathology, duration of treatment, etc. The potential for difficulty with discontinuation related to personality traits should be one of the factors weighted in the risk-benefit assessment made in the planning of benzodiazepine treatment for patients with anxious symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 18 publications
1
33
2
2
Order By: Relevance
“…This finding may not be surprising as high neuroticism scores have repeatedly been reported in the literature as negative predictors of treatment outcome, both in major depressive disorder patients treated either with medication [23,24] or with dynamic psychotherapy [25] and in GAD patients treated with medication or placebo [7,26,27,28]. Further, our group found a lower neuroticism and MMPI dependence score to be a consistent predictor of a favorable BZ discontinuation outcome in long-term BZ users [29,30]. Moreover, most recently Culpers et al [31] reported extremely high costs of neuroticism in the community, exceeding by far those of many psychiatric disorders.…”
Section: Discussionsupporting
confidence: 59%
“…This finding may not be surprising as high neuroticism scores have repeatedly been reported in the literature as negative predictors of treatment outcome, both in major depressive disorder patients treated either with medication [23,24] or with dynamic psychotherapy [25] and in GAD patients treated with medication or placebo [7,26,27,28]. Further, our group found a lower neuroticism and MMPI dependence score to be a consistent predictor of a favorable BZ discontinuation outcome in long-term BZ users [29,30]. Moreover, most recently Culpers et al [31] reported extremely high costs of neuroticism in the community, exceeding by far those of many psychiatric disorders.…”
Section: Discussionsupporting
confidence: 59%
“…For example, personality traits emerged as use-ful predictors of treatment outcome in patients with gastrointestinal disorders [5] , obesity [6] , hyperopia [7] and even individual responses to certain surgical treatments seem to be associated with personality [8,9] . In psychiatry, personality traits have been successfully linked to treatment outcome in depression [10] , anorexia nervosa [11,12] , schizophrenia [13] and withdrawal severity in benzodiazepine dependence [14] . In alcoholism research, personality traits have become a matter of scientific interest as well [15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Further, a higher level of psychopathology, especially anxiety and depressive symptoms, resulted in lower abstinence rates, as did the personality traits of neuroticism, dependence, and vulnerability (10,11,(15)(16)(17)(18). The impact of benzodiazepine withdrawal symptoms varies, probably owing to mediation by personality traits (16)(17)(18)20). However, neither the severity of benzodiazepine dependence nor the diagnosis of benzodiazepine dependence have been examined in relation to taper outcome (21), despite its apparent importance in long-term use (3).…”
mentioning
confidence: 99%